2009
DOI: 10.1024/1010-0652.23.34.223
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostische Fähigkeiten von Lehrkräften

Abstract: Diagnostische Fähigkeiten von Lehrkräften gelten als wichtige Voraussetzungen für die adäquate Vorbereitung, Durchführung und Nachbereitung des schulischen Unterrichts. Für den Unterricht sind wiederum in vielen Fächern Lernmaterialien grundlegend, die Texte mit instruktionalen Bildern enthalten. Vor diesem Hintergrund diente die vorliegende Studie der Untersuchung von zentralen Forschungsfragen zu Niveau und Zusammenhängen der diagnostischen Fähigkeiten von Lehrkräften im Bereich der Text-Bild-Integration, zu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
12

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(17 citation statements)
references
References 28 publications
0
5
0
12
Order By: Relevance
“…Participants who scored high on measures of intelligence also reached higher judgment accuracy when estimating the simulated students' correct answering rate. McElvany et al (2009) found a weak association between job experience and diagnostic competence. Other authors did not find evidence for the association of judgment accuracy with job experience (Impara & Plake, 1998) or with long-term teacher-student contact (Wild, 1993).…”
Section: Teacher Characteristicsmentioning
confidence: 92%
See 1 more Smart Citation
“…Participants who scored high on measures of intelligence also reached higher judgment accuracy when estimating the simulated students' correct answering rate. McElvany et al (2009) found a weak association between job experience and diagnostic competence. Other authors did not find evidence for the association of judgment accuracy with job experience (Impara & Plake, 1998) or with long-term teacher-student contact (Wild, 1993).…”
Section: Teacher Characteristicsmentioning
confidence: 92%
“…Teachers use their impressions of their students to create adequate learning environments for their classes and each student in it Therefore, teachers need to have the competencies to retrieve viable information on their students and apply this information in order to provide for adequate tasks (e.g., McElvany et al, 2009) and respond to their students' work with constructive feedback (e.g., Hattie & Timperley, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Auch in Beschreibungen zu diagnostischen Prozessen wird dies nur implizit erwähnt (Heitzmann et al 2019). Am ehesten kann dies als eine weitere Differenzierung des Urteilsbereiches aufgefasst werden (McElvany et al 2009). Eine Lernaus-gangslage sollte außerdem holistisch bestimmt werden.…”
Section: Die Diagnose Von Lernendenvorstellungenunclassified
“…Diagnosen können unterschiedliche personenbezogene Ebenen, wie bspw. eine lernendenglobale sowie eine lernendenindividuelle Ebene adressieren (McElvany et al 2009). Mit beiden Lernendenebenen werden verschiedene Diagnosesituationen assoziiert (Karst 2012;Karst et al 2014).…”
Section: Die Diagnose Von Lernendenvorstellungenunclassified
“…Sie untersuchen in erster Linie die Urteilsgenauigkeit von Lehrkräften in unterschiedlichen Fachdisziplinen (u.a. Spinath 2005, Südkamp et al 2008, McElvany et al 2009) und bringen durchaus unterschiedliche Ergebnisse hervor. So untersuchte beispielsweise Spinath (2005) eine Gruppe von 723 Grundschulkindern in Bezug auf ihre Intelligenzkennwerte sowie Selbsteinschätzungen hinsichtlich ihrer Fähigkeitswahrnehmung, Lernmotivation und Schulangst.…”
Section: Was Wir üBer Das Diagnostizieren Von Lesekompetenz Wissenunclassified